2021
DOI: 10.1136/bmj.m4447
|View full text |Cite
|
Sign up to set email alerts
|

Axial spondyloarthritis: new advances in diagnosis and management

Abstract: Axial spondyloarthritis (axSpA) is an inflammatory disease of the axial skeleton associated with significant pain and disability. Previously, the diagnosis of ankylosing spondylitis required advanced changes on plain radiographs of the sacroiliac joints. Classification criteria released in 2009, however, identified a subset of patients, under the age of 45, with back pain for more than three months in the absence of radiographic sacroiliitis who were classified as axSpA based on a positive magnetic resonance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
70
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 127 publications
(197 reference statements)
0
70
0
8
Order By: Relevance
“…The question of mechanical factors in the development and progression of axial spondyloarthritis (axSpA) is of great interest to the scientific community and inspires ongoing discussion among experts in the field [1,2]. Within this area of research, a special focus lies on the sacroiliac joints (SIJ), which biophysically act as the main transductor of force from the lower extremities to the torso [3] and are also by far the most common site of manifestation of axSpA [4]. Recent studies have found associations between the shape of the joints themselves and both inflammatory and degenerative joint disease [5•].…”
Section: Introductionmentioning
confidence: 99%
“…The question of mechanical factors in the development and progression of axial spondyloarthritis (axSpA) is of great interest to the scientific community and inspires ongoing discussion among experts in the field [1,2]. Within this area of research, a special focus lies on the sacroiliac joints (SIJ), which biophysically act as the main transductor of force from the lower extremities to the torso [3] and are also by far the most common site of manifestation of axSpA [4]. Recent studies have found associations between the shape of the joints themselves and both inflammatory and degenerative joint disease [5•].…”
Section: Introductionmentioning
confidence: 99%
“…We observed abnormal expression of TNF , NFKB , FOS , JUN , and JUNB in CD8+ T cells, and these genes were enriched in the TNF signaling pathway. The abnormal TNF signaling pathway in CD8+T cells plays a role in the pathogenesis of AS ( 37 ). The clinical application of anti-TNF therapy has changed the treatment of chronic inflammatory diseases, such as AS.…”
Section: Discussionmentioning
confidence: 99%
“…Социальная значимость аксиальных спондилоартритов (аксСпА) определяется их высокой распространенностью в популяции, дебютом заболевания в молодом возрасте (до 45 лет) и значительным вкладом болезни в потерю трудоспособности [1]. Внедрение в 1998/1999 годах в лечение аксСпА ингибиторов фактора некроза опухоли α (иФНО-α) коренным образом изменило течение аксСпА [2,3]. Первыми иФНО-α, применявшимися для лечения аксСпА, были инфликсимаб и этанерцепт (ЭТ), позднее появились адалимумаб, голимумаб, цертолизумаба пэгол [2,3].…”
Section: Introductionunclassified
“…Внедрение в 1998/1999 годах в лечение аксСпА ингибиторов фактора некроза опухоли α (иФНО-α) коренным образом изменило течение аксСпА [2,3]. Первыми иФНО-α, применявшимися для лечения аксСпА, были инфликсимаб и этанерцепт (ЭТ), позднее появились адалимумаб, голимумаб, цертолизумаба пэгол [2,3].…”
Section: Introductionunclassified